A new analytical framework of agile supply chain strategies. (26th November 2007) - Fujita, Yasunori
Today, fashion market is dynamic and stochastic. Customers' tastes are often influenced by the mood of the moment and fluctuate over time. As Christopher, Lowson and Peck (2004) pointed out, fashion market is 'chaotic' with the four characteristics (short life-cycles, high volatility, low predictability, and high impulse purchasing). Corresponding to such characteristics, it is increasingly important for the fashion retailers to react quickly and effectively to the changing markets. The present paper formulating the agile fashion supply chain system by making use of the optimal stopping theory, develops the agile strategy of a fashion retailer.